Localised sinonasal amyloidosis presenting with unilateral hearing loss: a case report and review of the literature - Suseeharan, Melanie; Dusu, Keli; Motter, Dema; Balfour, Alistair (International Surgery Journal, 2023)
Localised sinonasal amyloidosis is a rare occurrence with only twenty-nine documented cases in literature. This report follows the case of a 79-year-old gentleman with an atypical presentation of headaches and unilateral (right-sided) hearing loss. The patient initially underwent magnetic resonance imaging of his internal auditory meatus which was normal. Flexible nasoendoscopy was performed which identified a right middle meatus discharging possible polypoidal lesion. A computed tomography scan of his sinuses was performed which identified a large soft tissue lesion projecting into the upper nasal airway arising from the nasal recess, with the appearance suspicious for a polyp. Subsequently, the patient underwent functional endoscopic sinus surgery to manage right maxillary sinusitis and further examine the right-sided polypoidal mass lesion that was obstructing the maxillary antrum. Maxillary sinus biopsy revealed a diagnosis of sinonasal amyloidosis while tests for systemic amyloidosis were negative.